New Species of Asyndetus, Presumed Commensal Flies of Crabs, in Thailand (Diptera, Dolichopodidae, Diaphorinae) - GROOTAERT, PATRICK; MEUFFELS, HENK (Tropical Natural History, 2002)
Three Asyndetus species are described and illustrated from Thailand: A. ciliatus sp. nov., A. aciliatus sp. nov. and A. thaicus sp. nov.. The presence in Thailand of A. latifrons, a widespread Palaearctic and possibly Oriental species, is confirmed. A key is given for the four Thai species.